Development and optimization of microwave assisted process for extraction of onutmeg - NUKASANI SAGARIKA; Dr. Prince M. V (Guide) (Tavanur 2016 Department of Food and Agricultural Process Engineering)
Development and optimization of microwave assisted process for extraction of onutmeg
Development and optimization of microwave assisted process for extraction of onutmeg